Self Actualization in Hierarchy of Needs of a Princess as Seen in Meg Cabot’s the Princess Diaries - Raflis Raflis; Achreinzia Oktaviane (Fakultas Sastra Universitas Ekasakti, 2018)
The process of self-actualization and self-esteem, especially self-confidence and self-image of the main character in the novel The Princess Diaries by Meg Cabot. This novel tells about Mia Thermopolis, the freshman student at Albert Einstein High School. Like many other teens, Mia has a problem in self-confidence because of her body posture that she thinks does not meet the standard in general. Mia is often labeled as a freak in her school. Her life problem is getting more complicated when she knows that she is a princess from a small country in Europe. Mia’s problem is a picture of teenage problems in general, the lack of self-confidence and the bad self-image. But Mia learns to solve all of her life problems in a mature way and wish that she can reach her self-actualization. In this research, the writer uses descriptive research as the method of collecting the data. As for the method of analyzing the data, the writer uses structural method by understanding the novel, the character of Mia Thermopolis. Data collection technique uses qualitative technique with taking note cards in finding relevant data to the subject of analysis. In data analysis technique, the writer uses technique by interpreting data. The results of this research are: 1) Mia’s self-actualization process at the end of the novel only reach the self-esteem phase. Mia is not yet fully reach her self-actualization, she often still being selfish and mostly still being emotional. 2) Mia’s self-confidence at the end of the novel is increase, Mia can accept her own self and flaws. 3) Mia’s self-image at the end of the novel changed. Mia learns that what is important is not the appearance but the personality inside an individual. As closing, even though this novel looks light where the story is only about teenager’s life problem in general, but there are a lot of lessons that can be applied in the daily life. Maybe not every girl can be a princess in one night, but the lessons about how can we be confidence are a lot in this novel.